Exploring ‘Complex Adaptive Assemblage’ in Urban Design: A Case Study of Rethinking Informal Vendor Activities around Dhaka New Market Shopping Complex - Bhuian, Md. Ekramullah; Nusrat, Fahmida (Urban Planning and Construction, 2025)
The subject matter of Urban Design has long been criticised for having no substantial basis to formulate a significant groundwork of theoretical framework in general. Despite having the capability to formulate solutions in creative ways of thinking, Urban Design is subjected to further arguments regarding subject matters due to criticisms. While exploring this substantial amount of literature, this paper aims to put the process of urban design thinking into a hypothesis of the theoretical framework of “Complex Adaptive Assemblage”. In doing so, for more empirical purposes, a real-life scenario of informal vendor activities around a formal shopping complex in Dhaka city is chosen to explore the hypothesis. As a result, using the relevant understanding of the theoretical framework, a synergy is generated to analyze three design proposals aimed to accommodate informal vendor activities within the formal market area. An in-depth observation along with a pictorial survey has been conducted in three selected entry points of the retail premise that display the diverse agglomeration of the shoppers and vendors. The outcome discusses how the synergy works as a viable theoretical framework in the urban design thinking process. This theory-centric hypothetical urban design exercise for a real-life case study eventually has the potential to review the similar context of informal retail activities that is evident in many Global South countries.